Practical strategies for film-side sowing technology to enhance root lodging resistance and grain yield in spring maize on the loess plateau - Zhengyu Guo; Tingting Zhang; Kuo Chen; Jianlong Wu; Haoran Han; Wude Yang; Zhongdong Zhang (Scientific Reports)
Abstract In the spring maize cropping system, film-side sowing technology can improve crop yield stability and film recycling in the dry farming zone by optimizing the film cover pattern, resulting in a synergistic effect of moisture conservation, yield enhancement, and on-farm film residue management. However, the effect on the resistance to lodging is not clear. Consequently, a two-year agricultural trial was designed to evaluate how distinct ground-cover cultivation strategies influence root architecture, biomechanical performance, lodging incidence, grain production efficiency, and economic profitability. Three treatment factors were used in the experiment: planting without mulching (CK), planting under plastic-film mulch (UPM), and film-side sowing (FSS). The results showed that breaking strength and up rooting strength of FSS and UPM were increased by 46%, 37.2% and 53.1%, 47.2%, respectively, compared with CK. At the physiological maturity (R6), the root length density (RLD), root surface area density (RSAD), and root dry weight density (RDWD) rooting indicator of FSS were significantly higher than in UPM and CK within the shallow subsurface zone (0–20 cm), with increases of 76.5%, 66%, 65% and 35.5%, 33.6%, 39.6%, respectively. Likewise, the root indicators of FSS were 50.9%, 92.4%, and 68.5% larger than those of CK in the intermediate pedogenic zone (20–40 cm depth), respectively. However, apart from FSS, the among treatments within the deeper soil layer (40–60 cm interval) were not significantly different. The rate of lodging was significantly adversely correlated with the mechanical qualities (breaking strength, uprooting strength, and rind penetration strength), while root properties correlated well with these factors. In addition, the differences in root system indicators affected crop yield, which increased by 14.2% and 5% in FSS and UPM, respectively, compared with CK. Collectively, the highest seed yield and benefit and the lowest rate of lodging were observed under FSS conditions. The findings of this experiment will help to improve the cultivation measures to increase the resistance of spring maize to lodging.